Formulation and antibacterial evaluation of kombucha bar soap with varying concentrations of patchouli essential oil, Pogostemon cablin (Blanco) Benth. (Lamiaceae) against Staphylococcus aureus ATCC 25923 (Staphylococcaceae) - Meutia Khalida; Diannita Harahap (LPPM Universitas Negeri Jakarta, 2026)
The demand for natural antimicrobial agents in personal care products has grown as consumers seek safer and more sustainable alternatives to synthetic formulations. This study examined the development of kombucha-based bar soap incorporating varying concentrations of patchouli essential oil (0–3 %) using a Completely Randomised Design. Physicochemical properties, including pH, moisture content, foam height, and foam stability, were evaluated. Antibacterial activity against Staphylococcus aureus ATCC 25923 was assessed through inhibition zone measurements, while bioactive compounds were identified using Gas Chromatography–Mass Spectrometry (GC–MS). All formulations met the Indonesian National Standard (SNI). The resulting soap has an average pH of 8.0, a water content below 1 %, a foam height of between 5,80–6,50 cm and foam stability of between 77,5–91,5 %. The strongest antibacterial effect was observed with an inhibition zone of 10.67 mm. GC–MS analysis revealed patchouli alcohol and dodecanoic acid as the principal constituents, whose synergistic interaction is presumed to enhance antibacterial activity and product stability. The incorporation of kombucha and 3 % patchouli oil produced a formulation with favourable foaming properties, reliable stability, and promising potential for commercial application.